MELTING RATE CALCULATION ON PREHEATED WIRES OF VARIOUS CHEMISTRY UNDER ARC WELDING - Evgeny N. Varukha; Alexander S. Korobtsov; Igor S. Morozkin (Advanced Engineering Research, 2012)
The empirical factors dependences on the process parameters for the welding wires of various chemist ry are o btained for t he empirical formula permitting to calculate the wire melting rate (feed) in a wide range of current s, preheat temperatures, electrode diameters , and stick - outs under the welding in carbon dioxide on the reversed p olarity current. The calculation accuracy by the empirical formula and by the known computational melting model of the same wires is comparatively appraised. The effect of stick - out and preheat temperature increase of the welding wires on the productivity - boosting features of their melting is asse ssed.